EFIKASI DIRI DAN DUKUNGAN SOSIAL BERHUBUNGAN DENGAN KEPATUHAN HEMODIALISIS - Fitriani Agustina; Ainil Yusra (Poltekkes Kemenkes Aceh, 2022)
Patients with Chronic Kidney Disease (CKD) require renal replacement therapy, one of which is Hemodialysis (HD). HD that needs to be maintained to maintain the quality of life of CKD patients. Adequate hemodialysis can be achieved by increasing adherence to HD. The purpose of this study was to determine the relationship between self-efficacy and support for hemodialysis social compliance. The research design used cross sectional with consecutive sampling. This study involved 110 respondents. Collecting data using CKD Self Efficacy questionnaire, MOS social support survey and study documentation. Data analysis using Chi-Square test. The results showed that the proportion of patients who complied with hemodialysis was 60%, there was a significant relationship between self-efficacy (p= 0.000) and social support (p= 0.002) with HD adherence. The recommendation from this study is that nurses need to improve patient self-efficacy and involve social support to improve patient compliance with the hemodialysis program.